Impact of Technology Enhanced Video Feedback and Peer Evaluation on Gymnastic Performance in a Middle Years Program (MYP) International Baccalaureate Physical Education Class - Hutcheon, Andrew (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2021)
An analysis of the impact of technology-enhanced video feedback and peer evaluation on gymnastic performance in a MYP IB Physical Education class. A 5-step inquiry action research framework was employed; following the triangulation approach, both qualitative and quantitative data was collected to substantiate the findings. This study evidenced that peer feedback enhanced gymnastics performance, and that peer feedback when coupled with video analysis, further saw bolstered improvements. Suggesting both methods have a place in physical education, if conducted in the right manner. Adept use of appropriate technological tools would foster heightened intrinsic motivation and differentiated learning engagement.